Pembelajaran Ansambel Musik Angklung di SLB-C Negeri Pembina Kalimantan Selatan - Indah Dwi Noor Rakhmah (Pelataran Seni, 2016)
AbstractThis study aimed to describe the angklung ensemble learning in children with special needs in SLB-C Negeri Pembina Kalimantan Selatan. Aspects studied is about learning methods, the selection of teaching materials and evaluation of learning outcomes. From a qualitative approach-deskpirtif, as well as from the use of observation, interviews and documentation in data collection of this research, it is a picture that the methods used by teachers are: lectures, demonstrations, drill, frequently asked questions, gestures, and reward methods. Selection of instructional materials selected by adjusting the memory skills of students. The material is also delivered with the use of media numeral notation. For the evaluation of learning outcomes, using the teachers assess student performance tests while studying.Keywords: learning, ensemble music, angklung, children with special needs